All Roads Lead to... Italy: Costa Rican Poetry Translated into Italian - Vargas Gómez, Francisco Javier (2023)
The results of research on the translation of Costa Rican poetry into Italian are presented, including its evolution, determining factors, forms adopted, the image the translations project of the original poetry, and their potential function within the target context. It is concluded that the appearance of those translations would have been the result of opportunity and that, as poetic texts, they would have been adapted to the target readers’ expectations.